Recreational On-line Games and School Achievement in Adolescence: A Systematic Review and Meta-analysis - Karpouzi, Margarita; Serdari, Aspasia; Samakouri, Maria (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2024)
In the present study, we examined the effect of online games on school achievement during adolescence through systematic review and meta-analysis. The systematic review included 50 articles while 15 studies were selected for the meta-analysis. All studies covered the years 2012-2022 and described a sample of 217689 participants who used video games for recreational purposes and recorded the frequency of engagement. Initially, it was shown that the frequency of engagement with online video games, especially shooter games, has an effect on all age groups of adolescents but the effects are not dramatic. At the same time, it was shown that while excessive online gaming can hinder academic achievement, video games alone can promote skill acquisition and bring about positive academic outcomes. Interestingly, it is thanks to video games that a narrowing of the gap has emerged between men and women in terms of digital reading (Rasmusson & Åberg-Bengtsson, 2015).